'Thin' Regional Identities: Economic Instrumentality or Pathway to Thickness? The Case of the Pearl River Delta. (28th December 2022) - Lu, Haiyan; Braun, Erik; de Jong, Martin; Song, Yun; Zhao, Miaoxi
Abstract: Against the background of regional development, this article analyses the rise and fall of 'thin identities', which tend to be utilitarian and deployed to promote regional development. We focus on two constructed regional identities in the Greater Pearl River Delta (GPRD) in China: Pearl River Delta (PRD) and Guangdong‐Hong Kong‐Macau Greater Bay Area (GBA). We analyse the adoption of these identities through news items published in newspapers in both China's Mainland and Hong Kong. The results show that both economic and political events influence the adoption of thin identities, first PRD and then GBA. In the content analysis of news items, we investigate the pathways to their adoption and possible evolution towards thickness (broader social and cultural embeddedness) by distinguishing economic, political, social, and cultural topics. The wish of policymakers to adopt new thin identities, however, does affect the credibility of existing thick ones, a point deserving of serious consideration.